Buy online collect in-store: exploring grocery click&collect using a national case study. Issue 3 (3rd April 2019) - Davies, Alec; Dolega, Les; Arribas-Bel, Daniel
Abstract : Purpose: Twenty-first century online retailing has reshaped the retail landscape. Grocery shopping is emerging as the next fastest growing category in online retailing in the UK, having implications for the channels we use to purchase goods. Using Sainsbury's data, the authors create a bespoke set of grocery click&collect catchments. The resultant catchments allow an investigation of performance within the emerging channel of grocery click&collect. The paper aims to discuss these issues. Design/methodology/approach: The spatial interaction method of "Huff gravity modeling" is applied in a semi-automated approach, used to calculate grocery click&collect catchments for 95 Sainsbury's stores in England. The catchments allow investigation of the spatial variation and particularly rural-urban differences. Store and catchment characteristics are extracted and explored using ordinary least squares regression applied to investigate "demand per day" (a confidentiality transformed revenue value) as a function of competition, performance and geodemographic factors. Findings: The findings show that rural stores exhibit a larger catchment extent for grocery click&collect when compared with urban stores. Linear regression finds store characteristics as having the greatest impact on demand per day, adhering to wider retail competition literature. Conclusions display a need for further investigation (e.g. quantifying loyalty). Originality/value: New insights are contributed at a national level for grocery click&collect, as well as e-commerce, multichannel shopping and retail geography. Areas for further investigation are identified, particularly quantitatively capturing brand loyalty. The research has commercial impact as the catchments are being applied by Sainsbury's to decide the next 100 stores and plan for the next five years of their grocery click&collect offering.